Mammalian RNase H1 directs RNA primer formation for mtDNA replication initiation and is also necessary for mtDNA replication completion. Issue 15 (10th August 2022) - Misic, Jelena; Milenkovic, Dusanka; Al-Behadili, Ali; Xie, Xie; Jiang, Min; Jiang, Shan; Filograna, Roberta; Koolmeister, Camilla; Siira, Stefan J; Jenninger, Louise; Filipovska, Aleksandra; Clausen, Anders R; et al.
Abstract: The in vivo role for RNase H1 in mammalian mitochondria has been much debated. Loss of RNase H1 is embryonic lethal and to further study its role in mtDNA expression we characterized a conditional knockout of Rnaseh1 in mouse heart. We report that RNase H1 is essential for processing of RNA primers to allow site-specific initiation of mtDNA replication. Without RNase H1, the RNA:DNA hybrids at the replication origins are not processed and mtDNA replication is initiated at non-canonical sites and becomes impaired. Importantly, RNase H1 is also needed for replication completion and in its absence linear deleted mtDNA molecules extending between the two origins of mtDNA replication are formed accompanied by mtDNA depletion. The steady-state levels of mitochondrial transcripts follow the levels of mtDNA, and RNA processing is not altered in the absence of RNase H1. Finally, we report the first patient with a homozygous pathogenic mutation in the hybrid-binding domain of RNase H1 causing impaired mtDNA replication. In contrast to catalytically inactive variants of RNase H1, this mutant version has enhanced enzyme activity but shows impaired primer formation. This finding shows that the RNase H1 activity must be strictly controlled to allow proper regulation of mtDNA replication.